Drivers and policies for increasing and internationalising R&D activities of EU MNEs - Michele Cincera; Claudio Cozza; Alexander Tübke (European Commission, Joint Research Centre (JRC), 2010)
Based on an original and recent sample representative of the largest R&D corporations in the EU, this paper aims at investigating in a quantitative way the main factors explaining: (i) the decision of firms to increase their R&D investment effort in the near future; (ii) the main drivers explaining the favourite international location choice for R&D; and (iii) the impact of direct and indirect policies to support R&D activities in the EU. The main findings suggest that competitive pressures from the US are the main determinants for increasing R&D investments. Public support to R&D and proximity to other activities of the company influence the decision to locate R&D in the home country. Considerations on the cost of employing researchers become one factor among others only for firms preferring a location outside their home country, in particular in the rest of the world (countries other than the EU or the US).
Keywords: F23; O32; 330; Drivers of R&D internationalisation; R&D policies; EU large R&D corporations